2013
DOI: 10.4172/2157-7471.1000183
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of Root-Knot Nematode (Meloidogyne javanica) On Olive in the Greenhouse conditions

Abstract: This experiment was conducted regarding the Fifth Development Plan, suggesting that olive cultivation in the province, Khouzestan, is developing and according to reports of the researchers of Research Center for Agriculture and Natural Resources of the province announcing that 75 percent of greenhouses and seedling production centers of the province have been infested and polluted by the root-knot olive nematode and that the infected plants, due to production costs, must somehow be disinfected and free of nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Actually, chemical treatments mostly have the advantage of the quick and effective response in controlling plant-parasitic nematodes. Soltani et al (2013) found that aldicarb, enzone, oxamyl, and cadusafos at 6 and 8 ppm concentrations were effective treatments in controlling the root-knot nematode, M. javanica, on 1-year old olive seedlings in the greenhouse.…”
Section: Resultsmentioning
confidence: 97%
“…Actually, chemical treatments mostly have the advantage of the quick and effective response in controlling plant-parasitic nematodes. Soltani et al (2013) found that aldicarb, enzone, oxamyl, and cadusafos at 6 and 8 ppm concentrations were effective treatments in controlling the root-knot nematode, M. javanica, on 1-year old olive seedlings in the greenhouse.…”
Section: Resultsmentioning
confidence: 97%
“…Researchers throughout the world have become increasingly interested in diminishing the use of chemical strategies against parasites [ 81 , 82 , 83 ]. A recent study has demonstrated that some species of edible Basidiomycetes such as Pleurotus species possess nematicidal activity through the production of a nematode-toxin, which is able to inhibit the nematode movement, allowing hyphal penetration, and finally digesting the body by enzymatic action [ 84 ].…”
Section: Biocontrol Properties Of Basidiomycetesmentioning
confidence: 99%
“…Effective nematode management remains challenging, with chemical control employing nematicides emerging as the most reliable strategy (Chen et al, 2020). Nematicides such as Furadan 5G, Vydate 24 L, Rugby 10 G, Aldicarb, Enzon, Oxamyl, and Cadusafos have demonstrated efficacy in reducing root-knot nematode infections and enhancing plant growth (Faruk et al, 2011;Soltani et al, 2013). Thus, this study aims to explore novel nematicides to mitigate nematode damage and bolster plant productivity.…”
Section: Introductionmentioning
confidence: 99%